Between Realpolitik And Islamic Solidarity: A Critical Evaluation Of Indonesia's Foreign Policy On The Gaza Conflict Under President Prabowo Subianto - Muhamad Barqi Asila (CV. SINAR HOWUHOWU, 2026)
Indonesia's foreign policy towards the Gaza conflict under President Prabowo Subianto has sparked intense public debate regarding the nation's moral positioning in international relations. While Indonesia consistently voices support for Palestinian independence through diplomatic channels and humanitarian aid, its participation in multilateral